Skills development or talent identification? An exploration of sport development initiatives in three previously disadvantaged communities in Tshwane, South Africa - Botha, J.; van der Klashorst, E. (African Journal for Physical Activity and Health Sciences, 2020)
The development of skilled athletes and players is an important step towards creating a winning sporting nation. Even though there are a variety of approaches that can be used to develop the sport skills of young athletes, the overall consensus is that this process takes time. This study explores the sport development approach currently used in sport development programmes in the previously disadvantaged communitiesa of Atteridgeville, Eersterust and Mamelodi in Tshwane, South Africa, by distinguishing between two phases in sport development, namely talent identification and skills development. The study utilised a qualitative research approach with key informant sampling comprised of sport administrators and coaches involved in sport development. Data were collected by means of document analysis and semi-structured interviews which were transcribed and coded using Atlas.ti 8 software. It was concluded that the current sport development initiatives available to athletes aged between 7 and 18 years, residing in previously disadvantaged communities in Tshwane portray characteristics of talent identification rather than a skills development approach. Recommendations include provision of additional support to non-governmental organisations (NGOs) active in providing young athletes the opportunity to develop both sport and life skills in Sport for Development (SfD) initiatives.